The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1007/bf01577745
|View full text |Cite
|
Sign up to set email alerts
|

Subperiosteal intraorbital haematoma following minor head trauma

Abstract: Subperiosteal haematoma of the orbit following minor head trauma is extremely rare. A 5-year-old girl is presented with bilateral proptosis, chemosis, extraocular palsy, and progressive visual loss after minor head trauma. She had no evidence of fracture or abnormality of coagulation. The intraorbital haematoma resulted most probably from the oozings of a subgaleal haemorrhage which entered the subperiosteal space and then dissected over the supraorbital ridge into the orbit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Six patients returned to 20/20 vision after surgery; 1 improved to 20/30, 12 1 remained no light perception, 5 1 was lost to follow-up, 13 and for 2 it was only indicated that "orbital swelling resolved" without a note of visual acuity. 10,14 Six reported cases had bleeding disorders: 15 (Factor IX deficiency [Christmas disease] 16 and heterozygous Factor VII deficiency). 7 Another patient was diagnosed with von Willebrand factor deficiency the development of SGH after minor scalp trauma (hair braiding).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six patients returned to 20/20 vision after surgery; 1 improved to 20/30, 12 1 remained no light perception, 5 1 was lost to follow-up, 13 and for 2 it was only indicated that "orbital swelling resolved" without a note of visual acuity. 10,14 Six reported cases had bleeding disorders: 15 (Factor IX deficiency [Christmas disease] 16 and heterozygous Factor VII deficiency). 7 Another patient was diagnosed with von Willebrand factor deficiency the development of SGH after minor scalp trauma (hair braiding).…”
Section: Discussionmentioning
confidence: 99%
“…Hair pulling ( by other children while playing) 6,9,11 3 Hair pulling (child abuse by mother's boyfriend) 1 1 Hair braiding 17 1 "Minor" head trauma 14 1 Fall from bike 5 1 Assault (karate chop to head) 13 1 Struck head at home while playing* 4 2 Struck head on playground pole 16 1 Fall while roller skating 7 1 Struck by falling frying pan 10 1 Punch to parietal region by sibling 12 1 *our patient.…”
Section: Literature Searchmentioning
confidence: 99%
“…Sinusitis, coagulophaties, complications of ophtalmologic procedures, sinus or cranial surgery, and even labor are related among the systemic causes. Spontaneous intraorbital hematomas without any predisposing factor are very rare [6][7][8][9][10][11] . When the hematoma presents as diplopia, proptosis or other symptons and signs, without loss of visual acuity or signs of elevated intraocular pressure, some authorities advocate a trial of conservative management, ranging from observation alone to topical use of timolol maleate and intravenous or oral carbonic anhydrase inhibitors (acetazolamide).…”
Section: Discussionmentioning
confidence: 99%